Transformation of Islamic Religious Education Policy Towards Religious Moderation - Dina Kamilia; Saiful Hadi; Juhairiyah Juhairiyah (Penerbit Presisi Pustaka, 2026)
The changing times bring new challenges for religious education, particularly the emergence of extreme and intolerant religious attitudes among some members of society. This condition highlights the need for a new approach to religious education that is more open and contextual. Therefore, PAI policies need to adapt to the digital era by utilizing technology in the dissemination of moderation values and strengthening critical and wise religious literacy. This research uses qualitative research thru a literature study (Library Research) approach, which involves gathering information from several books, journals, and other references relevant to the topic or problem under discussion. The research results indicate that the reform of Islamic Religious Education (PAI) policies toward religious moderation has produced positive changes while also providing valuable lessons for the future of Islamic education in Indonesia. The success achieved serves as a strong foundation for taking further steps in building a religious and tolerant society.